P1-S1.13 Heterogeneity of the HIV epidemic in the general population of Karnataka state, India. (10th July 2011) - Banandur, P; Potty, R S; Mahagaonkar, S B; Bradley, J; Banadakoppa, R M; Washington, R G; Blanchard, J F; Moses, S; Lowndes, C M; Alary, M
Abstract : Background: In the context of AVAHAN—The India AIDS Initiative of the Bill and Melinda Gates Foundation, general population surveys (GPS) have been carried out in three Karnataka districts in India. Given the north-south gradient already observed in HIV prevalence in antenatal population in Karnataka districts, we analysed data from three such surveys to detect heterogeneity. The three districts analysed here are Belgaum (Northern Karnataka), Bellary (middle of the state) and Mysore (Southern Karnataka). Methods: We conducted a comparative analysis of these three GPS conducted between 2005 and 2007. Subjects were selected using a two-stage cluster sampling design with equal number of rural and urban participants, and of men and women, with a target sample size of 6000 per district. Questionnaires on socio-demographic factors and HIV risk behaviour were administered. Blood samples were tested for HIV, syphilis and HSV-2 antibodies, whereas urine samples were tested for gonorrhoea and chlamydia using nucleic acid amplification tests. A descriptive analysis of prevalence of HIV and sexually transmitted infections (STIs) was conducted according to age, district and place of residence (rural/urban). Results: Abstract P1-S1.13 table 1 shows HIV prevalence per district according to gender and place of residence. Belgaum had the highest overall HIV and HSV-2 prevalence (16.9%) and the lowest prevalence of curable STIs (Chlamydia—0.38%; Syphilis—0.42%) among the three districts. Women in Belgaum had a higher HIV prevalence (OR=2.16, 95% CI—1.02 to 4.58) compared to women in Mysore. The HIV epidemic in Belgaum is predominantly rural and among women. In Bellary, it is predominantly urban and among men. Mysore had the lowest prevalence of HIV and HSV-2 (10.9%) and the highest prevalence of curable STIs (Chlamydia—1.05%; Syphilis—1.38%) among the three districts. There were only six cases of gonorrhoea in total (five in Mysore and one in Bellary). Conclusion: The HIV epidemic in Karnataka shows considerable heterogeneity. This analysis validates the observed north-south gradient. The sex work structure in these three districts might explain the heterogeneity of the HIV epidemic in these three districts. Higher prevalence of HIV and HSV-2 and lower prevalence of curable STIs in Belgaum suggests a late epidemic phase. Mysore may have an early phase epidemic with higher prevalence of curable STIs.